Media-Literacy Rate of Certified Elementary School Teachers in Bandar Lampung City - . Herpratiwi; Ujang Suparman; . Sugiyanto (International Conference on Education and Language (ICEL), 2013)
The objective of the research is to investigate the rate of media-literacy of certified elementary school teachers in Bandar Lampung City. The method of the research is quantitative. The data were collected by means of questionnaire and test based on individual competence framework. The sample was 230 teachers selected by means of random sampling technique, that is, 10% out of 2300 teachers. The rate of media-literacy of certified elementary school teachers in Bandar Lampung City was found to be at the basic level because the score was under 70. The teachers’ ability to operate media was not high enough, their ability to analyze the content of the media was not high, and their ability to communicate by means of media was also very limited.